A case study of L1 interference in speech acts among Chinese L2 students - Pramela Krish,; Oh, Chen May (Penerbit Universiti Kebangsaan Malaysia, 2020)
Improving linguistic and communicative competence will minimise challenges faced in Intercultural communication especially with globalisation and technology advancement. The study aimed at identifying potential areas of L1 interference in speech production relating to five speech acts: compliments, requests, refusals, apologies, and complaints. The L1 interference is examined based on four approaches which are Contrastive Analysis, Error Analysis, Interlanguage Analysis, and Contrastive Rhetoric. Data was collected through a discourse completion task comprising five speech acts: compliments, requests, refusals, apologies, and complaints, and an interview to find out students’ reasons for committing L1 interferences. The findings revealed lexical, discourse and syntactic interferences in the students’ speech where students faced difficulties in understanding the different semantic systems between Chinese and English, were influenced by cultural knowledge and transferred linguistic rules from their L1 to the L2. The main reasons for these interferences were lack of opportunities for practice and limited vocabulary repertoire. Therefore, it is important to develop ways to improve linguistic and communicative competence to minimise misunderstanding and awkward sentences in speech communication.